Demographic Security of Russia: Regional Measures, Results Estimation - S. V. Soboleva; N. E. Smirnova; O. V. Chudaeva (Мир новой экономики, 2018)
The central part of the article is presentation of methodical approach to the analysis of the demographic situation dynamics on several indicators for multiple territorial objects, allowing evaluating each territory according to the degree of the demographic situation tension in general. For this type of analysis several indicators of demographic threats has been selected, on which the dynamics for regions of the Siberian Federal District (SFD) on the background of the all-Russian tendencies has been presented. The integral indicator of demographic security is also used (IIDS). Having compared the dynamics of IIDS for all subjects of the SFD three groups of regions in terms of demographic security in 1990-2014 are selected. It is shown that almost all regions with a low level of demographic security are the border territories of the Russian Federation, having the state borders with Kazakhstan, Mongolia and China. Thus, these regions require special attention from the authorities of different levels and the adoption of appropriate management decisions in order to remedying the situation in the field of demographic security. IIDS elaboration represents the scientific and practical interest, since it allows to look after the demographic situation in the whole on the territory of region, the Federal District or the country, analyze its dynamics and do comparative analysis across time and space. This IIDS can be used to develop measures of demographic policy at the federal and regional levels, as well as taking other managerial decisions to ensure demographic security.